Evaluasi Program Pelayanan Online Kartu Keluarga, Akta Pencatatan Sipil dan Surat Keterangan Pindah di Nagari Binjai Kabupaten Pasaman - Sonia Fitri, Yola; Malau, Hasbullah (Policy, Law and Political Research Center, 2023)
This study aims to describe the evaluation of the implementation of the online service program for family cards, civil registration deeds and moving certificates in Nagari Binjai, Tigo Nagari District, Pasaman Regency. This research is motivated by the fact that in Nagari Binjai there are still many people who have not updated their population documents and the community is still providing direct services at the Population and Civil Registration Office of Pasaman Regency, the low level of public knowledge of this program, certainty of service time, and inadequate internet network. in performing online services in Nagari Binjai. This type of research is descriptive qualitative research. This data the authors get through interviews and documentation studies. The results of the study indicate that the implementation of the online service program for family cards, civil registration certificates and transfer certificates has been running in Nagari Binjai, but has not been fully effective, efficient in accordance with the predetermined objectives.